AGE AND EMOTIONAL CHARACTERISTICS OF CHILDREN REPATRIATED FROM TERRORIST ACTIVITY ZONES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The article talks about the age and emotional characteristics of children repatriated from zones of terrorist activity.